Graphite thermal expansion coefficient measured by in-situ x-ray diffraction - Abdullah, M.A. (Institute of Physics Publishing, 2020)
Precision temperature measurement of a nano system with high sensitivity and fast response is still a challenge. The marvelous thermal and mechanical properties of graphite will allow the creation of superior nanoscale temperature sensors. In-situ x-ray diffraction was employed to determine the graphite hexagonal crystal lattice dimensions and the coefficient of thermal expansion based on the calculation of its interatomic distance. The energy of graphite was mapped over the first Brillouin zone in the temperature range of 50 °C-1200 °C at intervals of 50 °C. Energy-based comparative studies between the quantum free electron approach obtained by an inelastic scattering and an harmonic oscillator are introduced by the principal quantum number associated with the excitation level. The hexagonal lattice constants, interlayer distance and interatomic distance of graphite crystals are investigated analytically with consideration given to their temperature dependence and the carbon peak (002), where the 2θ value decreases slightly with increasing temperature. The coefficient of thermal expansion of graphite-based interatomic distance is negative and tends toward zero with increasing temperature, which is in very good agreement with experiments. Moreover, the energy probability distributions enclosed by reciprocal lattice vectors of the hexagonal lattice are defined and interpreted based on lattice dimensions with varying temperature. Linear changes of the temperature-driven unit cell lattice dimensions and analysis of the kinetic energy of the electron in graphite may both be utilised for the advanced temperature interpretation model and preliminary design of a precise nanothermometer. © 2020 IOP Publishing Ltd.